Wallet Payments Recent Potential Threats and Vulnerabilities with its possible security Measures - Bosamia, Mansi; Patel, Dharmendra (International Journal of Computer Sciences and Engineering, 2019)
The volume of wallet payment transactions has considerably increased in the last decade. There are many wallets already has been developed and also new wallets coming in the market day by day for payment transactions in highly distributed environments. So far it has the focus on addressing only security issues. However, key important criteria of distributed processing such as performance, scalability, and availability. In this paper, we identify and analyze the different threats and vulnerabilities of a mobile cum web wallet application to obtain a high-level understanding of the various types of threats that may affect wallet applications with its possible security measures.